Optimalisasi Human Resource Management Dengan Metode AHP Untuk Pemberian Bonus Karyawan PT. Talang Gugun Sari Nusantara - Yuliandri, Mario; Muhammad, Abulwafa; Lusinia, Shary Armonitha (Jurnal Sains Informatika Terapan, 2025)
PT Talang Gugun Sari Nusantara already has dozens of employees in each branch, each employee has various criteria in every job. Therefore, PT Talang Gugun Sari Nusantara has a way to improve the performance of every employee. By giving bonuses to employees who do their work well and in accordance with the Company's wishes. PT Talang Gugun Sari Nusantara previously conducted an assessment in a manual way that made its assessment irrelevant to the circumstances that occurred. With this problem, the company needs a Decision Selection System using the Analysis Hierarchy Process method to assess employees with several criteria such as attendance, sales of each employee, responsibility, and manners. The research conducted aims to build a software on "Optimizing Human Resource Management by Determining the Provision of Bonuses to Employees of Pt. Talang Gugun Sari Nusantara Using the Analytical Hierarchy Process (AHP) Method". In this study, a case was raised, namely looking for the best alternative based on the criteria that had been determined by using. This method was chosen because it was able to select the best alternative from 4 criteria. In this case, the intended alternative is those who are entitled to receive employee bonuses based on the specified criteria. This research was carried out by finding the value weight of each attribute and then a ranking process was carried out that would determine the optimal alternative, namely employees receiving bonuses.